'Kids know about art': Amplifying under-represented voices in art museums through mentorship. Issue 3 (1st December 2016) - Reid, Natasha S.; Cinquemani, Shana; Farrar, Chelsea
Within this article, we share our experiences critically engaging with and elevating under-represented voices in museum spaces via a graduate level course in multicultural museum education. We bring the perspectives of both an assistant professor and two graduate students in order to explore multi-faceted relationships grounded in trust, risk-taking, non-hierarchical dynamics and co-mentorship. Natasha (as assistant professor) explores her experiences developing and implementing the assignment and related course, highlighting how her relationship with these graduate students enabled her to develop a more fluid approach to mentorship. Chelsea and Shana (as graduate students) examine their interpretation and implementation of the assignment, and their reciprocal and non-authoritative relationship with their child participant. Finally, we collaboratively reflect on the experience through a dialogue at the end of the article. We aim to offer readers insight regarding how assignment design, interpretation, and the chosen site for implementation can support dynamic and alternative mentorship opportunities that emphasize the amplification of under-represented voices.